2022
DOI: 10.7717/peerj-cs.854
|View full text |Cite
|
Sign up to set email alerts
|

An ensemble based approach using a combination of clustering and classification algorithms to enhance customer churn prediction in telecom industry

Abstract: Mobile communication has become a dominant medium of communication over the past two decades. New technologies and competitors are emerging rapidly and churn prediction has become a great concern for telecom companies. A customer churn prediction model can provide the accurate identification of potential churners so that a retention solution may be provided to them. The proposed churn prediction model is a hybrid model that is based on a combination of clustering and classification algorithms using an ensemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…(2021) 26 0.9300 0.8110 Bilal et al . (2022) 27 0.9243 0.7181 0.9470 0.8063 Karuppaiah and Gopalan (2021) 28 0.8900 Rabbah et al . (2022) 29 , 0.8350 0.8190 Karamollaoglu et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2021) 26 0.9300 0.8110 Bilal et al . (2022) 27 0.9243 0.7181 0.9470 0.8063 Karuppaiah and Gopalan (2021) 28 0.8900 Rabbah et al . (2022) 29 , 0.8350 0.8190 Karamollaoglu et al .…”
Section: Resultsmentioning
confidence: 99%
“…Bilal et al . 27 introduced a CP model based on hybrid clustering and classification methods to predict customer churn from two publicly available datasets. The results showed that this model is more robust than the other existing models in the literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of model improvement, numerous scholars have adopted ensemble learning methods: S. De constructed a novel stacked framework based on various basic data mining algorithms [25]. Fakhar Bilal and Xiahou each adopted an ensemble strategy of clustering before classification [26,27]. Karuppaiah used a stacking method based on Bayesian, gradient boosting trees, and support vector machines to build models [28].…”
Section: Related Workmentioning
confidence: 99%
“…According to Singh & Sivasankar (2019), Bagging could achieve a prediction accuracy of over 0.80. Moreover, the study by Bilal et al (2022) The study of Badawi et al (2019) provided evidence that the stacking model is preferable to the Bagging, boosting, and individual models in terms of accuracy and dependability in various situations. Bokaba et al (2022) conducted a study that demonstrated the superior performance of the stacking model compared to other models in terms of accuracy, precision, recall, and F1-score in predicting road traffic congestion.…”
Section: Supervised Machine Learningmentioning
confidence: 99%